How New Technologies Are Changing Typography: Breaking Tyranny of Arial. - Bloomer, Peggy (International Journal of the Book, 2014)
Since the dominance of Microsoft Word and until the introduction of the @font-face CSS style, typography has been reduced to one typeface per layout--usually Arial. Increasingly, the manufacturing of type has moved from the foundry to the software company. Foundries have remained the provenance of the designer, not the general public. However, that is changing with the introduction of new Font APIs (Application Programming Interface). Websites and layouts have rediscovered display fonts, serif fonts, and specialty fonts once again, which raises a lot of questions about the future of typography. Will this spawn a new generation of ransom note typography, or is something else on the typographic horizon? Will there be a return to the time-honored rule of three fonts to a layout that developed as the de facto principle restrainting fonts in traditional book publishing? Using the serif font for ease of readability saw a marked decline in the years of Web 1.0. Have the use of CMSs (Content Management Systems) like WordPress put an end to that dominance? What is the impact of on-demand printing on typography, where so much publishing is generated through Word, instead of Adobe InDesign or Quark Xpress? As the deployment of content becomes more global, what fonts support a wide variety of language glyphs? This paper will attempt to look at these issues and focus on the influence of websites and Web 2.0 themes. In addition, examples of these current usages and the impact of globalization in web and printing distribution and font usage will be examined in order to showcase the expanding use of font APIs and their impact on typographic usage.